La figure dans le poème : traits et retraits - Aurore Clavier (Caliban: French Journal of English Studies, 2016)
In the wake of the hidden figures which, from James to Gilman, tormented narrators of the late 19th century, modernist poets were obsessed with images, whether they represented a topos to be destroyed or rather provided a writing paradigm. Yet, between the lines of this literary history lies a middle-ground where figures seem the most blatant when they vanish, a place where their very disappearance has the impact of an apparition. Chasing form down to its most concealed recesses or losing itself into its most unreadable meanders, the poem does not sketch the contours of a space so much as it beats a particular time, seeking to reproduce the secret pulse of the visible, through the opening of its design.